Comparison Study of Indonesian Third-Culture Individuals and Non-Third Culture Individuals in Regards to Communication Accommodation in Intercultural Business - Tarisa Karlina Marentek; Sharon Schumacher (Conference Series, 2020)
Third Culture Individuals (TCI) are people who spent a significant amount of time outside their passport country during their developmental years. Due to their exposure to different cultures, they are inclined and have the ability to adjust their communication and behaviour accordingly. Communication Accommodation focuses on Convergence and Divergence, the communication strategies when individuals adapt to each other’s communication language and behaviour. Convergence occurs when individuals adjust their communication to be more similar to their communication partner. Conversely, Divergence is when individuals accentuate differences. The aim of this study is to compare communication Convergence and Divergence levels of Indonesian TCI and non-TCI by adopting a pre-existing scale measuring four dimensions (Approximation, Interpretability, Discourse Management and Interpersonal Control). Data was gathered through an online survey with 140 respondents who are Indonesian TCI and non-TCI. Results show that even though both groups are convergent, TCI are more convergent and accommodating.. Communication Accommodation Theory, Convergence and Divergence, Intercultural Communication, Cultural Identity, Intercultural Business Communication, TCK, Third Culture Kids, Third Culture Individuals